Left sinus of valsalva aneurysm ruptured into left ventricle: A case report of 320-multidetector CT findings. Issue 23 (June 2017) - Bae, Kyungsoo; Jeon, Kyung Nyeo; Lee, Hyang-im; Jang, Jeong Yoon; Park, Sung Eun; Ryu, Kyeong Hwa; Baek, Hye Jin; Choi, Bo Hwa; Moon, Jin Il; Cho, Soo Buem
Abstract: Rationale: Ruptured aneurysm originating from the left coronary sinus of Valsalva into the left ventricle (LV) is extremely rare. Imaging features of sinus aneurysm has been commonly reported using echocardiography or angiography. Here, we report multidetector computed tomography (MDCT) findings of left sinus of Valsalva aneurysm extending into the LV and caused severe aortic regurgitation (AR) in a 44-year-old male with latent infective endocarditis. The role of MDCT in preoperative surgical planning was also emphasized. Patient concerns: The patient visited our hospital due to worsening exertional dyspnea for 3 months. Diagnoses: On cardiac computed tomography (CT) using 320-MDCT, a saccular aneurysm arising from the left coronary sinus of Valsalva extending into the LV was diagnosed as the cause of severe AR. Interventions: The patient underwent resection of the aneurysm, aortic root reconstruction, and aortic valve replacement. Outcomes: The patient made an uneventful recovery. Follow-up echocardiography showed no paravalvular leakage with improved LV function. Lessons: MDCT with wide coverage and high temporal resolution can provide exact and comprehensive information about complicated conditions, leading to confident surgical planning and successful management.